2003
DOI: 10.1227/01.neu.0000044131.03495.22
|View full text |Cite
|
Sign up to set email alerts
|

Differential Gene Expression in Human Cerebrovascular Malformations

Abstract: OBJECTIVE-We sought to identify genes with differential expression in cerebral cavernous malformations (CCMs), arteriovenous malformations (AVMs), and control superficial temporal arteries (STAs) and to confirm differential expression of genes previously implicated in the pathobiology of these lesions. NIH-PA Author ManuscriptNIH-PA Author Manuscript NIH-PA Author Manuscript METHODS-Total ribonucleic acid was isolated from four CCM, four AVM, and three STA surgical specimens and used to quantify lesion-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(67 citation statements)
references
References 42 publications
4
61
0
2
Order By: Relevance
“…Sensitivity of VZV arrays. The relative abundance of individual transcripts within an RNA preparation is most accurately determined by array analysis when the probe is labeled during first-strand cDNA synthesis (17,40). Whereas direct cDNA labeling of VZV-infected cell mRNA yielded probe with activity sufficient to detect numerous VZV transcripts, labeling the synthesized cDNA by nick translation yielded probes with higher activity.…”
Section: Resultsmentioning
confidence: 99%
“…Sensitivity of VZV arrays. The relative abundance of individual transcripts within an RNA preparation is most accurately determined by array analysis when the probe is labeled during first-strand cDNA synthesis (17,40). Whereas direct cDNA labeling of VZV-infected cell mRNA yielded probe with activity sufficient to detect numerous VZV transcripts, labeling the synthesized cDNA by nick translation yielded probes with higher activity.…”
Section: Resultsmentioning
confidence: 99%
“…9 Research characterizing cerebrovascular lesions has demonstrated increased expression of angiogenic factors, such as VEGF-A, at the protein and mRNA levels. 19,20 In such lesions, normal adult cerebral vascular growth is stopped, endothelial cell proliferation and angiogenesis are in a relatively inhibited state and VEGF-A expression is low. 21 Such findings may indicate that in cAVM angiogenesis is in an active state, especially in H-AVM, and that endothelial cell proliferation and angiogenesis are more active, which may also explain the causes of haemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…73 Perhaps > 300 genes are upregulated and almost 560 are downregulated in cerebral vascular malformations. 111 These genes encode growth factors, cell adhesion and ECM factors, inflammatory factors, MMPs, and endocrine hormones. Different cell types, including endothelial cells, vascular SMCs, and inflammatory cells, have been examined to understand the pathogenesis of AVMs.…”
Section: Molecular Biology Of Avms: Vegf Tgfβ and Angsmentioning
confidence: 99%